KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN MEMBELI AIR MINERAL AQUA - Iga Maghfirah Deviana; Elimawaty Rombe; Rahmat Mubaraq (Jurnal Ilmu Manajemen Universitas Tadulako (JIMUT), 2018)
This research aims to know and analyze: (1) the influence of product quality and brand image to consumer's decision to buy AQUA brand mineral water at Faculty of Economics in Tadulako This research aims to: 1) determine and analyze simultaneous influence of product quality and brand image on consumers’ decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (2) determine and analyze the influence of product quality on consumers’ decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (3)determine and analyze the influence of brand image on consumers’ decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University. The type of research is quantitative. The Population consists of students in The Faculty of Economics who bought AQUA brand mineral water. Sampling technique is purposive to select 100 respondents. Data collection is questionnaires. Method of analysis is multiple linear regressions. The result indicates that: (1) product quality and brand image simultaneously influence consumer's decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (2) product quality has partial influence on consumer decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (3) brand image has partial influence on consumer decision to buy mineral water of AQUA brand in Faculty of Economics of Tadulako University.    Penelitian ini bertujuan untuk mengetahui dan menganalisa: (1) pengaruh kualitas produk dan citra merek terhadap keputusan konsumen membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako, (2) pengaruh kualitas produk terhadap keputusan konsumen membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako, (3) pengaruh citra merek terhadap keputusan konsumen membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako. Jenis penelitian yang digunakan adalah kuantitatif (menunjukkan hubungan antar variabel). Populasi dalam penelitian ini adalah mahasiswa Fakultas Ekonomi yang membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako. Teknik penarikan sampel dalam penelitian ini menggunakan purposive sampling, dengan jumlah sampel sebanyak 100 responden. Pengambilan data menggunakan kuesioner. Metode analisis menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa (1) Terdapat pengaruh kualitas produk dan citra merek terhadap keputusan konsumen membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako, (2) Terdapat pengaruh kualitas produk terhadap keputusan konsumen membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako, (3) Terdapat pengaruh citra merek terhadap keputusan konsumen membeli air mineral merek AQUA di Fakultas Ekonomi Universitas Tadulako.